Study of stress degradation and determination of the stability of the substance and injection solution of sodium 2-((4-amino-5-thiophen-2-ylmethyl)-4h-1,2,4-triazol-3-yl)thio)acetate - Usenko, D. L.; Kaplaushenko, A. G.; Усенко, Дмитро Леонідович; Каплаушенко, Андрій Григорович (My University, 2024)
Research goal. The aim of the work was to investigate stress degradation and determine the stability of the substance and injection solution of sodium 2-((4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazol-3-yl)thio)acetate (API) to determine storage conditions and establish shelf life. Research materials. The substance API was synthesized earlier. The chromatographic system used was Agilent 1260 Infinity HPLC, equipped with a diode array detector and a single quadrupole mass spectrometric detector Agilent 6120. Software was OpenLAB CDS. Methods, research results, and their discussion. The stability determination procedure of the substance and injection solution involves maintaining the dosage forms at a temperature higher than the average storage temperature and constant monitoring of the quantitative content of the active substance during storage. Investigation of stress-induced thermal degradation was conducted in a dry heat oven. Additionally, samples of sodium 2-((4-amino-5-thiophen-2-ylmethyl)-4H-1,2,4-triazol-3-yl)thio)acetate with hydrogen peroxide, 0.1 M alkali, and 0.1 M acid were kept at room temperature for 4 days. The influence of ultraviolet (UV) irradiation on the substance and solution of sodium 2-((4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazol-3-yl)thio)acetate was also investigated. HPLC system was used to monitor the quantitative content of the active substance. It has been established that the shelf life of substance API and a 1% solution of sodium 2-((4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazol-3-yl)thio)acetate is at least 2 years. Hydrogen peroxide and ultraviolet radiation have the greatest impact on sodium 2-((4-amino-5-(thiophen-2-ylmethyl)-4H-1,2,4-triazol-3-yl)thio)acetate, so it is recommended to store the observed objects in conditions free from solar radiation. Процедура визначення стабільності субстанції та ін’єкційного розчину включає утримання лікарських форм у разі температури, вищої за середню температуру зберігання, та в процесі зберігання постійний контроль кількісного вмісту діючої речовини. Дослідження стресової термічної деградації проводилось у сухожаровій шафі, крім того, зразки натрій 2-((4-аміно-5-тіофен-2- ілметил)-4H-1,2,4-тріазол-3-іл)тіо)ацетату (АФІ) з H2O2, 0.1 М лугу і 0.1 М кислотою тримали за кімнатної температури протягом 4 днів. Також досліджено вплив ультрафіолетового випромінювання на субстанцію і розчин АФІ. Для контролю кількісного вмісту діючої речовини використали систему Agilent 1260 Infinity HPLC, діодно-матричний детектор та одноквадрупольний мас-спектрометричний детектор Agilent 6120 з іонізацією в електроспреї.
Дослідження стресової деградації і визначення стабільності субстанції та ін’єкційного розчину натрій 2-((4-аміно-5-тіофен-2-ілметил)-4h-1,2,4-тріазол-3-іл)тіо) ацетату
Keywords: 1,2,4-triazoles; active pharmaceutical ingredient; shelf life; stress degradation; parenteral dosage form; 1,2,4-тріазоли; активний фармацевтичний інгредієнт; термін придатності; стресова деградація; парентеральна лікарська форма